Retroduction, reflexivity and leadership learning: Insights from a critical realist study of empowerment. Issue 4 (September 2019) - Willis, Paul
This article contributes to leadership learning by discussing how retroduction can be used to enhance the reflexive capabilities of a professional group. The study shares insights from a critical realist research project to illustrate how the application of retroductive inference in interview design supports an investigation of the contextual constraints preventing practitioners from enacting desired leadership behaviours. This focus considers retroduction's potential as a stimulus intended to encourage a practical, conversational and collaborative form of reflexivity between researcher and research participant. The leadership context investigated concerns the work place experiences of senior corporate communicators who express a desire to be empowering leaders. The study shows how the interplay between retroduction and reflexivity can enhance understanding of the conditions under which knowledge is enacted, or rather not enacted, in a specific leadership context. The article then highlights how the learning generated by the research was used to inform the development of a reflexive process which has since been applied in a range of professional learning environments. The discussion of its application contributes to the growing scholarly interest in reflexive pedagogy, meeting the need for alternative approaches to leadership learning which reconnect with context and explore the influence of power.